EdU-Based Step-by-Step Method for the Detection of Sister Chromatid Exchanges for Application in Plant Genotoxicity Assessment - Kwasniewska, Jolanta; Bara, Adrianna (Frontiers in Plant Science, 2020)
This study is the example of using 5-ethynyl-2`-deoxyuridine (EdU) for detecting sister chromatid exchanges (SCEs) at chromosomal level. Here we report a detailed protocol for differential labeling sister chromatids in barley (Hordeum vulgare, 2n=14) cells that is based on the incorporation and simple detection of EdU. The perfect distinguishing of sister chromatids enabled an analysis of the effects of two model agents - maleic acid hydrazide (MH) and gamma rays, on the formation of SCEs. Using this method, we demonstrated the high sensitivity of barley cells to maleic hydrazide, which is expressed as an increased level of SCEs. A gamma ray induced only slightly more SCEs in the treated cells than in the control cells. The possible mechanisms of MH and gamma ray action in respect to distinguishing chromatids using EdU are discussed. Recommendation for SCEs visualization using EdU as an easy and quick method that can be successfully adapted to other plant species and potentially for human genotoxicity studies is presented.